Global health challenges: Are future physicians prepared? The results of a 4 years training experience. (30th September 2020) - Sisti, L G; Frisicale, E M; Corsaro, A; Parente, P; Riccardi, M T; Villani, L; Barbara, A; Di Pietro, M L; Ricciardi, W; Bruno, S
Abstract: Background: Current health challenges are highlighting as Global Health (GH) is a discipline of growing importance for future physicians. Although its training is globally recommended, it has not universally entered the curricula of degree courses in Medicine and Surgery. A cycle of 6 seminars in global health has been promoted by researchers and public health residents of the Center for Research and Studies in GH of the Università Cattolica del Sacro Cuore (UCSC) in Rome, and offered for 4 consecutive years to medical students attending the UCSC. Objectives and Methods: Main goal was increasing students knowledge and awareness in global health issues exploring their needs and perceptions about the impact of the topic on their future career. Two-hours frontal lessons held by experts and practical sessions (PBL) facilitated by promoters were planned on topics as determinants and inequalities in health, UHC, fragile and vulnerable population as migrants and victims of violence, SDGs, AIDS and emerging infectious diseases, international cooperation, maternal-child health. A pre-course, single event and post-course questionnaire was administered to participants. Results: A mean of 48 students (± 15.7SD), 66.7% females, attending mainly the second(40.4%) and the third year (39%), joined each event. The analysis of the pre-course questionnaire has highlighted students' interest in healthcare inequalities, pandemics, migration, health in developing countries, healthcare systems. At the end, 92% of participants has considered the course interesting, 87% stated that the topic should be part of the degree course and 78% that it will influence their career. The methodology was considered adequate in 94% of cases underlining its strong incentive to work in team. Conclusions: The strong interest of medical students in acquiring skills in global health seems to firmly encourage its inclusion and strengthening in study plans to prepare them properly to face the future challenges in health. Key messages: Medical students consider the global health training relevant for their career encouraging its inclusion in the Medicine and Surgery curriculum. Practical sessions and team work could be useful tools to adequately train the future health workforce.